2002
DOI: 10.1097/00008571-200204000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Variation in coumarin 7-hydroxylase activity associated with genetic polymorphism of cytochrome P450 2A6 and the body status of iron stores in adult Thai males and females

Abstract: The relationships between catalytic activity of cytochrome P450 2A6 (CYP2A6), polymorphism of CYP2A6 gene, gender and levels of body iron stores were analysed in a sample group of 202 apparently healthy Thais, aged 19-47 years. Eleven individuals were found to have high activity of CYP2A6, judged by the relatively large amounts (11.2-14.6 mg) of 7-hydroyxcoumarin (7-OHC) excreted 3 h following administration of 15 mg of coumarin. Ten individuals, however, did not excrete any 7-OHC. Of these 10, four were found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
28
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 42 publications
2
28
0
Order By: Relevance
“…Two of these studies showed a statistically significant 98 difference; 17% higher 3-h urinary excretion of 7-hydroxycoumarin in females compared with males was reported by Ujjin et al (2002), and the study by Iscan et al (1994) showed 11% higher 7-hydroxycoumarin excretion in women compared with men in a 2-h coumarin test. A third study showed significantly higher activity in women compared with men only in a subpopulation with lower coumarin hydroxylase activity (Xu et al, 2002c).…”
Section: Gender-related Differences In Nicotine Metabolism I Difmentioning
confidence: 95%
See 1 more Smart Citation
“…Two of these studies showed a statistically significant 98 difference; 17% higher 3-h urinary excretion of 7-hydroxycoumarin in females compared with males was reported by Ujjin et al (2002), and the study by Iscan et al (1994) showed 11% higher 7-hydroxycoumarin excretion in women compared with men in a 2-h coumarin test. A third study showed significantly higher activity in women compared with men only in a subpopulation with lower coumarin hydroxylase activity (Xu et al, 2002c).…”
Section: Gender-related Differences In Nicotine Metabolism I Difmentioning
confidence: 95%
“…A tendency for higher metabolism in women compared with men has been detected in most (six of seven studies) of the phenotyping studies using coumarin 7-hydroxylation or conversion of caffeine metabolite 1,7-dimethylxanthine to 1,7-dimethyluric acid as a measure of CYP2A6 activity (Rautio et al, 1992;Iscan et al, 1994;Sotaniemi et al, 1996;Krul and Hageman, 1998;Nowell et al, 2002;Ujjin et al, 2002;Xu et al, 2002c). Two of these studies showed a statistically significant 98 difference; 17% higher 3-h urinary excretion of 7-hydroxycoumarin in females compared with males was reported by Ujjin et al (2002), and the study by Iscan et al (1994) showed 11% higher 7-hydroxycoumarin excretion in women compared with men in a 2-h coumarin test.…”
Section: Gender-related Differences In Nicotine Metabolism I Difmentioning
confidence: 99%
“…First, sex differences in CYP2A6 activity have been reported. For example, the urinary excretion level of 7-hydroxycoumarin formed from coumarin by CYP2A6 was significantly higher in women than in men (Iscan et al, 1994;Ujjin et al, 2002). The ratio of cotinine/nicotine in plasma was higher in women than in men (Nakajima et al, 2006a).…”
mentioning
confidence: 94%
“…Twenty-six allelic variants of CYP2A6 have been identified to date, resulting in altered enzyme activity that affects the metabolism of substrates ranging from pharmaceuticals to toxins including procarcinogens (Raunio et al, 2001). Although interindividual variation in CYP2A6 levels has been attributed to physiological factors (Ujjin et al, 2002), inflammatory disease (Kirby et al, 1996), pharmaceutical exposure (Sotaniemi et al, 1995;Pelkonen et al, 2000), and genetic polymorphisms within the CYP2A6 coding region (Raunio et al, 2001), little is known about CYP2A6 transcriptional regulation and its involvement in the observed variation in expression.…”
mentioning
confidence: 99%